A case study of detecting anomalous signals prior to the great 2010 Maule earthquake - Shen Wenbin; Ding Hao (Geodesy and Geodynamics, 2013)
The Hilbert-Huang transform (HHT) is used to analyze the time series from nine superconducting gravimeter (SG) stations and 22 broadband seismometers to investigate the anomalous signals prior to the great 2010 Maule earthquake. The results show that seven SG time series and 20 broadband seismometer time series have anomalous signals lasting about one to three days before the earthquake occurrence. The anomalous signals appear around the frequency bands 0.07Hz and 0. 15Hz in SG records while around the frequency band 0. 13Hz −0. 2Hz in seismic records, and the reason why they appear in different bands might be attributed to the intrinsic nature and different sensitivities of different kinds of instruments. Because more than 87% records have the anomalous signals prior to the earthquake, and no typhoon event is found in our chosen time window, we may conclude that the anomalous signals might be precursory signals of the great 2010 Maule event. However, we do not rule out other possible excitation sources.